Women entrepreneurs and the global environment for growth : a research perspective - Brush, Candida G. (Cheltenham; Northampton, MA : Edward Elgar, 2010)
The book provides wide-ranging insights on the challenges that women entrepreneurs face growing their businesses and how these may be addressed. This volume is rooted in research and considers growth challenges, both contextually and firm specific, provoking current thought and enriching the current literature on gender and entrepreneurship.
Includes bibliographical references and index
nif 16/05/13, ijb 21/02/2019
Loan
Keywords: Entrepreneurship; Businesswomen